The Role of Social Media in Building the Brand Image of Islamic Business for Young Entrepreneurs - Hasibuan, Putri; Irwanto, Irwanto; Ulandari, Ulandari; Aulia, Anggi; Azwar, Khairul (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
The development of digital technology has brought significant changes to business marketing strategies, particularly among young Muslim entrepreneurs. Social media has become a creative, effective, and cost-efficient space for developing the brand image of Islamic businesses. This study employs a library research method by examining theories, academic journals, and previous research findings related to digital branding strategies, social media, and Islamic business. The results indicate that social media plays an important role as a medium for communicating Islamic values reflected in products, services, and business ethics. The utilization of platforms such as Instagram, TikTok, and YouTube is able to enhance public trust, expand market reach, and build an authentic and religious brand image. Through Islamic content strategies, testimonials, storytelling, and active interaction, young entrepreneurs can strengthen their business positioning and compete fairly in the modern market.